Conflicts and conflict resolution in international anti-trust : do we need international competition rules? - Klodt, Henning (2001)
Introduces the effects doctrine and the comity principles, which are at the heart of international anti-trust co-operation. Explores the scope for international cooperation on the base of 20 anti-trust case studies. Focuses on the rising importance of anti-trust issues for the sustainability of the international trading order.